THE CRYSTAL STRUCTURE OF STRONALSITE AND A REDETERMINATION OF THE STRUCTURE OF BANALSITE - Liferovich R.P.; Mitchell R.H.; Locock A.J.; Shpachenko A.K. (My University, 2006)
The structures of stronalsite, SrNa2Al4Si4O16, and banalsite, BaNa2Al4Si4O16, have been determined by direct methods using single-crystal X-ray diffractometry with a CCD area detector. The structures are topologically identical and adopt the non-centrosymmetric space-group Iba2 rather than the centrosymmetric space-group Ibam previously ascribed to banalsite. Unit-cell parameters are: a 8.4080(9), b 9.8699(11), c 16.7083(18) Å, V 1386.6(3) Å3, Z = 4, Dcalc. 2.92 g/cm3 for stronalsite (Khibina massif, Kola, Russia); a 8.5400(7), b 10.0127(9), c 16.7897(14) Å, V 1435.7(2) Å3, Dcalc. 3.05 g/ cm3 for banalsite from Wales (Benallt mine, UK), and a 8.5068(16), b 9.9811(18), c 16.7485(31) Å, V 1422.1(5) Å 3,,Dcalc. 3.08 g/cm3 for banalsite from Långban (Sweden). The structures are built on an infinite framework of corner-sharing tetrahedra, with Si and Al being completely ordered at four independent sites. Alternately pointing up (U) and down (D) Si(1)-Al(1) and Si(2)-Al(2) tetrahedra form four- and eight-fold rings parallel to the (001) plane, resulting in a -UDUD- framework, which differs from the -UUDD- framework of feldspars. The stacking results in six-fold rings parallel to the (100) plane. The interstices of the framework are occupied by large Sr or Ba atoms (xA2+), and smaller VINa+, ordered at alternate levels parallel to (001), and separated by 1/4 c. The isostructural character of banalsite and stronalsite accords well with the complete solid-solution Bal-xSrxNa2 Al4Si4O16 occurring in nature.